2015
DOI: 10.1155/2015/854070
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury Molecule-1 and Cardiovascular Diseases: From Basic Science to Clinical Practice

Abstract: Despite the recent findings concerning pathogenesis and novel therapeutic strategies, cardiovascular disease (CVD) still stays the leading cause of morbidity and mortality in patients with renal dysfunction, especially acute kidney injury (AKI). Early detection of patients with impaired renal function with cardiovascular risk may help ensure more aggressive treatment and improve clinical outcome. Kidney injury molecule-1 (KIM-1) is a new, promising marker of kidney damage which is currently the focus of countl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 91 publications
0
42
0
5
Order By: Relevance
“…In our study, KIM-1 levels were not significantly different among the groups. Although KIM-1 is a new, promising marker of kidney damage [26], some studies reported that KIM-1 levels are associated with glomerular filtration, but not with other urinary tubular damage markers [27, 28], and that the levels of KIM-1 differentiated poorly between patients with good or poor outcomes [28]. Other studies found that KIM-1 predicted the progression of kidney damage [29] or AKI in patients who underwent cardiac surgery [30].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, KIM-1 levels were not significantly different among the groups. Although KIM-1 is a new, promising marker of kidney damage [26], some studies reported that KIM-1 levels are associated with glomerular filtration, but not with other urinary tubular damage markers [27, 28], and that the levels of KIM-1 differentiated poorly between patients with good or poor outcomes [28]. Other studies found that KIM-1 predicted the progression of kidney damage [29] or AKI in patients who underwent cardiac surgery [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study involving 62 patients undergoing renal transplant has shown that KIM-1 levels in kidney tissues were significantly elevated in all patients who developed AKI. For patients with acute rejection, the rate reached even 92% [47].However, there was no significant change in AKI patients with complicated nephrotic syndrome [44,48].…”
Section: Kidney Injury Molecule 1 (Kim-1)mentioning
confidence: 96%
“…Within the past 2 decades, a few novel potential biomarkers ( Table 1) that are measurable in urine or plasma of patients with AKI have been identified [49], including neutrophil gelatinase-associated lipocalin (NGAL) [17,50,51], kidney injury molecule 1 (KIM-1) [27,52], interleukin 18 (lL-18) [53], liver-type fatty acid-binding protein (L-FABP) [54], tissue inhibitor of metalloproteinase 2 (TlMP-2), insulin-like growth factorbinding protein 7 (IGFBP7) [33], calprotectin [42], urine angiotensinogen (AGT) [55], and urine microRNAs [47,56].…”
Section: 94mentioning
confidence: 99%
“…Studies investigating KIM-1 as a biomarker of AKI have shown variable results [27,52,98,99]. In patients with congestive heart failure, Damman et al recently demonstrated that KIM-1 is an outstanding predictive marker for AKI detection [100].…”
Section: Kidney Injury Moleculementioning
confidence: 99%